The Nagorno-Karabakh conflict in the context of the foreign policy of Iran in the Transcaucasus at the end of XX the beginning of XXI century - A. A. Tolokneva (Гуманитарные и юридические исследования)
Introduction. The events of 2020 in NagornoKarabakh have actualized the problem of conflict resolution in the region. Iran has been one of the actors in the negotiation process between the Armenian and Azerbaijani sides since the early 90s. For reasons of national security, this direction has become the most important in Iran’s foreign policy activities in the Transcaucasus. The article focuses on the position taken by Iran regarding the Nagorno-Karabakh conflict in 1992-2018. Iran believed that it could become an alternative to Western states in the negotiation process. The article examines the most important aspects of Iranian-Armenian and Iranian-Azerbaijani relations during the indicated period. The influence of the interests of Iran in the field of economics, logistics, production of energy resources, and the energy sector on the position of Tehran regarding the conflict has been revealed. The article pays attention to the attitude of Armenia and Azerbaijan to the Iranian nuclear program in the context of interstate relations and regional security. The problem of the Zangezur corridor is considered as one of the most important aspects of the contradictions between Baku and Yerevan and affecting the building of the national security of Iran. Materials and Methods. The study analyzes official documents, statements and statements by officials of Iran, Armenia and Azerbaijan around the problem of resolving the Nagorno-Karabakh conflict in 1992-2018. To study the problem, comparativehistorical, narrative and problemchronological research methods are used. Analysis. The article reveals the influence of the Nagorno-Karabakh conflict factor on building Iran’s national security in the region. The policy of Tehran towards Azerbaijan and Armenia is traced in the context of regional security. Results. The study concluded that national security interests force Iran to act as a mediator in resolving the Nagorno-Karabakh conflict. The official position of Tehran was to prevent the escalation of the conflict and resolve the problem through political negotiations. One of the aspects of the position of Iran was the prevention of direct or indirect interference in the conflict by the United States, NATO, the EU, etc. To this end, Tehran carried out activities to attract regional actors (Turkey, the Russian Federation) for a joint dialogue with the Azerbaijani and Armenian sides. Iran proceeded from the interests of ensuring national security when building a balanced position in relations with Azerbaijan and Armenia.